2006
DOI: 10.1038/nn1822
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis for modulation of Kv4 K+ channels by auxiliary KChIP subunits

Abstract: KChIPs coassemble with pore-forming Kv4 alpha subunits to form a native complex in the brain and heart and regulate the expression and gating properties of Kv4 K(+) channels, but the mechanisms underlying these processes are unknown. Here we report a co-crystal structure of the complex of human Kv4.3 N-terminus and KChIP1 at a 3.2-A resolution. The structure reveals a unique clamping action of the complex, in which a single KChIP1 molecule, as a monomer, laterally clamps two neighboring Kv4.3 N-termini in a 4:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
198
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(215 citation statements)
references
References 35 publications
17
198
0
Order By: Relevance
“…Definitely, more research is needed to elucidate the role of Ca 2+ in Kv4/KChIP complex formation. In this regard it should also be noted that both the Kv4 N-terminus and the Kv4 tetramerization (T1) domain contribute to KChIP binding [31,74], and each KChIP subunit interacts with the N-terminus of one and the T1-domain of a neighboring Kv4 α-subunit [30,75]. It is possible that the Ca 2+ dependencies of KChIP binding to these two sites differ.…”
Section: Ca2+ Dependence Of Kv4/kchip Complex Formation and Membrane mentioning
confidence: 99%
See 1 more Smart Citation
“…Definitely, more research is needed to elucidate the role of Ca 2+ in Kv4/KChIP complex formation. In this regard it should also be noted that both the Kv4 N-terminus and the Kv4 tetramerization (T1) domain contribute to KChIP binding [31,74], and each KChIP subunit interacts with the N-terminus of one and the T1-domain of a neighboring Kv4 α-subunit [30,75]. It is possible that the Ca 2+ dependencies of KChIP binding to these two sites differ.…”
Section: Ca2+ Dependence Of Kv4/kchip Complex Formation and Membrane mentioning
confidence: 99%
“…The N-terminal KIS domain of KChIP4a, which also harbors an ER retention motif, is made responsible for these trafficking and gating effects [15,81]. In the KChIP4a splice variant the hydrophobic groove, which represents a binding domain of KChIPs for the Kv4 N-terminal helix [30,75,82], can be occupied by its own N-terminal helix in vitro (Figure 2(c)), and it was suggested that it may have to be competed out by the Kv4 N-terminus to allow Kv4/KChIP4a complex formation [83,84]. With KChIP2x and KChIP3x (= KChIP3b) Jerng and Pfaffinger [85] have identified two brain KChIP isoforms, which, like KChIP4a, contain an N-terminal KIS domain.…”
Section: Ca2+ Dependence Of Kv4/kchip Complex Formation and Membrane mentioning
confidence: 99%
“…Cite this article as Cold Spring Harb Perspect Biol 2010;2:a004085 conformational change on binding to their target proteins (Ames et al 2006;Pioletti et al 2006;Strahl et al 2007;Wang et al 2007) (Fig. 2).…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 99%
“…We nonetheless wish to emphasize that we are not questioning results of prior crystallographic studies demonstrating the existence of two KChIP binding sites in the K v 4.3 N-terminal domain (proximal "site 1" and T1 "site 2"). 18,19 Rather, our results functionally indicate that both KChiP2b and 2d do not exert pronounced effects on D2-39 macroscopic inactivation kinetics, but nonetheless still accelerate recovery. We thus propose that KChiP2-mediated modulation of native for D2-39 + KChiP 2d is illustrated in Figure 1 (main panel), and overlaid with the mean D2-39 (basal conditions) and D2-39 + KChIP 2b recovery waveforms (obtained using the identical protocol) reported in our prior analysis.…”
mentioning
confidence: 59%